ECONOMIC GROWTH AND REGIONAL DEVELOPMENT DISPARITY IN SOUTH SULAWESI - Razak, Abd. Rahman (Economic Journal of Emerging Markets, 2013)
This study aims to analyze the relationship between economic growth and disparity of regional economic development in regencies/cities of South Sulawesi. The Klassen Typology and Williamson Index are adopted to plot the rate of economic growth and income disparity during 2005-2010. The results show that the development of economic in the City of Parepare and Palopo and Regency of North Luwu are able to create simultaneously higher economic growth rate and more equitable distribution of income. While the other regions are not able to reach those two indicators of regional development at the same time including the more advance economics of Makassar City. Keyword: Economic growth, regional development disparity, Klassen Typology, Williamson Index JEL classification numbers: O40, R10